2009
DOI: 10.1128/iai.00417-09
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Systemic Brucella melitensis Infection through the Digestive Tract Requires Urease, the Type IV Secretion System, and Lipopolysaccharide O Antigen

Abstract: Human brucellosis is caused mainly by Brucella melitensis, which is often acquired by ingesting contaminated goat or sheep milk and cheese. Bacterial factors required for food-borne infection of humans by B. melitensis are poorly understood. In this study, a mouse model of oral infection was characterized to assess the roles of urease, the VirB type IV secretion system, and lipopolysaccharide for establishing infection through the digestive tract. B. melitensis strain 16M was consistently recovered from the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 57 publications
3
80
0
Order By: Relevance
“…Previous studies have described hepatic and splenic microgranulomas during systemic infections with pathogenic Brucella spp. in the mouse (13,25,34). In this study, these same histopathological changes were observed mainly at 7 and 30 dpi, i.e., in chronic stages of B. ovis infection.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Previous studies have described hepatic and splenic microgranulomas during systemic infections with pathogenic Brucella spp. in the mouse (13,25,34). In this study, these same histopathological changes were observed mainly at 7 and 30 dpi, i.e., in chronic stages of B. ovis infection.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, the mouse has frequently been used as an infection model to study chronic infections with Brucella spp. (2,13,21,34,43). In this study, we developed and characterized a murine model for B. ovis infection for up to 90 dpi in male BALB/c and C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of clinical signs observed in this study was longer compared to intraperitoneal inoculation of Brucella immunogens (Abdullah et al, 2013). These findings could be explained by a study conducted by Grillo et al (2012) that stated that only low proportion of bacteria (1 to 2%) will translocate through the gut cells as the digestive tract holds many defenses towards colonization and multiplication of pathogenic microorganisms (Paixao et al, 2009).…”
Section: Discussionmentioning
confidence: 54%
“…The pathogens are then shed to the environment in large numbers through the placenta, vaginal fluids and milk (Megid et al, 2010). This facultative intracellular bacterium is able to invade into and survive within macrophages and non-professional phagocytes which results in its ability to cause chronic infection in the host (Paixao et al, 2009;Sa et al, 2012). Brucella does not evade phagocytosis by macrophages or neutrophils but inhibits the degranulation of both primary and secondary neutrophil granules and the myeloperoxidase-hydrogen peroxide-halide system.…”
Section: Introductionmentioning
confidence: 99%
“…While lipid A and core OS structures are relatively conserved, the OAg is highly diverse, giving rise to thousands of O-specific serotypes among Gram-negative bacteria. In certain bacteria, the OAg plays a role in pathogenesis by influencing macrophage recognition and resistance to the lytic action of the complement system (3,25,26,32), epithelial cell invasion (7,38), and intracellular survival (27).…”
mentioning
confidence: 99%